TINJAUAN YURIDIS ANAK BELUM DEWASA SEBAGAI TURUT TERGUGAT DALAM SENGKETA WARIS (STUDI PUTUSAN PENGADILAN AGAMA SUKABUMI NOMOR 0371/PDT.G/2017/PA.SMI) - Intan Justiasari; Muriani Muriani (Reformasi Hukum Trisakti, 2021)
The Sukabumi Religious Court Decision Number 0371/Pdt.G/2017/PA.Smi concerns. It has to do with the legal subject being a minor and the exception being slander. The question put forth is: Can a immature child be dropped as a co-defendant in a case brought before the court? And what justifies the Sukabumi Religious Court's panel of judges rejecting the defendant's exception to the inheritance claim for obscenity libel? The research is descriptive in nature, uses secondary data, is processed in a qualitative manner, and draws findings based on deductive reasoning. The research approach is juridical-normative. Decision Number 0371/Pdt.G/2017/PA.Smi, which was based on the findings of the investigation, discussion, and conclusions, found that the because there were parties who were immature and who were not being represented by their legal adult, the lawsuit had formal flaws and was not legally valid. This was determined by a judge. The claim is therefore unacceptably false as a result. The reason for the judge's consideration breaches the process for modifying a case, thus it is not in compliance with the applicable law.